PARP inhibition sensitizes childhood high grade glioma, medulloblastoma and ependymoma to radiation - Vuurden, Dannis G. van; Hulleman, Esther; Meijer, Olga L. M.; Wedekind, Laurine E.; Kool, Marcel; Witt, Hendrik; Vandertop, W. Peter; Würdinger, Thomas; Noske, David P.; Kaspers, Gertjan J. L.; Cloos, Jacqueline (OncoTarget, 2011)
https://doi.org/10.18632/oncotarget.362 Dannis Gilbert Van Vuurden, Esther Hulleman, Olga L.M. Meijer, Laurine E. Wedekind, Marcel Kool, Hendrik Witt, W. Peter Vandertop, Thomas Würdinger, David P....
Gesehen am 07.12.2022